Conceptualizing and determining core clinical competencies in nursing students: a qualitative study. (19th August 2019) - Moradi, Y.; Ahmadi, F.; Sadeghi, A.; Oshvandi, K.
Abstract : Aim: This study aimed to conceptualize and explain the core clinical competencies of nursing students in Iran. Background/Introduction: Despite the national and international efforts to modify nursing curricula such that the students' clinical competencies are improved, there is still a widespread concern about this issue, perhaps due to the impact of factors other than the curriculum itself, such as the lack of a clear definition for the concept of clinical competency and its main components in nursing students. Methods: This qualitative study was conducted using conventional content analysis. The participants were selected through purposive sampling and included 14 senior students of bachelor of nursing, four nurses working in teaching hospitals and six clinical instructors. Individual semi‐structured interviews were used for data collection. After recording and transcribing the interviews, content analysis was used to extract the concepts. Findings: The main theme of the study was 'multidimensionality of the concept of clinical competency, ' which had six main categories, namely 'adoption of and adaptation with the nursing practice, ' 'nursing knowledge, ' 'self‐direction in clinical learning, ' 'patient care skills, ' 'professional ethics' and 'the development of professional behaviours.' Discussion/Conclusion: Clinical competency and its dimensions among students comprise a multidimensional concept. Having a clear and comprehensive understanding of this concept and focusing on its core axes may be the most important step in improving students' clinical competency. Implications for nursing, health and education policy: Policymakers and nursing education authorities can identify the problems existing in the students' clinical competency and provide them with practical solutions for a standard professional education through a clear understanding of the concept of clinical competency and its dimensions.